Good Agricultural Practice (GAP) Trials in Brinjal: A Step Toward Safer, Nutritious, and Secure Food Systems in Bangladesh - Quamruzzaman, A K M; Rabiul Islam, M.; Akter, L.; Ziaur Rahman, A.K.M.; Mezba, Md. Sayed Ali; Salam, M. A.; Moni, Z. R.; Hassan, M. S. (Discoveries in Agriculture and Food Sciences, 2025)
To validate the Good Agricultural Practices (GAP) standards, a trial of brinjal (variety: Caity) from Ispahani Seed Company was conducted at a farmer’s field in Shibpur, Narsingdi, Bangladesh, during the summer season of 2024. The objective was to produce high-quality and safe brinjal following GAP guidelines. The Government of Bangladesh officially authorized the Bangladesh GAP protocol in 2023, providing a framework for producers to cultivate high-quality crops for consumers. All activities in this trial adhered to the Bangladesh GAP protocol to ensure superior brinjal production. A total of 37 decimals of land, owned by Md. Belayet Hossain was planted with brinjal on March 13, 2024. The crop was managed strictly according to GAP standards. Harvesting took place over a period from May 8, 2024, to July 26, 2024, with a total of 22 harvests. The first harvest was conducted on May 8, 2024, while the final (22nd) harvest occurred 168 days after transplanting, on July 26, 2024. The entire yield was obtained from the 37-decimal plot, with fruit yield per harvest varying depending on the harvest time. The yield ranged from 69.69 kg to 206.19 kg per plot. A similar trend was observed in the fruit yield per hectare, which ranged from 465.23 kg/ha to 1,376.46 kg/ha. These values represent single-harvest yields. The total fruit yield from the 37-decimal plot was 3,045 kg, while the estimated yield per hectare was 20,331 kg. These findings indicate that brinjal production under GAP standards can ensure high-quality yields, contributing to both local and export markets. The economic analysis of brinjal production reveals a positive return on investment, as indicated by the Benefit-Cost Ratio (BCR) of 1.31.